Identifying 'at-risk' critically ill patients who present to the emergency department and require intensive care unit admission: A retrospective observational cohort study. Issue 3 (May 2021) - Crilly, Julia; Sweeny, Amy; O'Dwyer, John; Richards, Brent; Green, David; Marshall, Andrea P.
Abstract: Background: Emergency department (ED) triage is the process of prioritising patients by medical urgency. Delays in intensive care unit (ICU) admission can adversely affect patients. Objectives: This study aimed to identify characteristics associated with ICU admission for patients triaged as Australasian Triage Scale (ATS) 3 but subsequently admitted to the ICU within 24 h of triage. Methods: This retrospective, observational cohort study was conducted in a public teaching hospital in Queensland, Australia. Patients older than 18 y triaged with an ATS 3 and admitted to the ICU within 24 h of triage or admitted to the ward between January 1, 2012, and December 31, 2012, were included. The demographic and clinical profiles of ICU admissions vs. all other ward admissions for patients triaged an ATS of 3 were compared. Multivariable regression analysis compared characteristics of patients triaged with an ATS of 3 who did and did not require ICU transfer. Descriptive data are reported as n (%) and median and interquartile range (IQR). Regression analysis is reported as adjusted odds ratios (aORs) with 95% confidence intervals (95% CIs). Results: Of the 27 454 adult ED presentations triaged with an ATS of 3, 22.4% (n = 6138) required hospital admission, comprising 5302 individuals, 2.1% of whom (n = 110) were admitted to the ICU within 24 h of triage. Age- and sex-adjusted predictors of ICU admission for patients triaged with an ATS of 3 included infectious (aOR: 3.7; 95% CI: 2.0–6.9), neurological (aOR: 2.8; 95% CI: 1.6–5.0), and gastrointestinal disorders (aOR: 2.2; 95% CI 1.2–3.5); arriving by ambulance; arriving after hours; or arriving on weekends. Regardless of diagnosis or sex, persons older than 80 y were less likely to be admitted to the ICU (aOR: 0.4; 95% CI: 0.2–0.8). Conclusions: Patients triaged as ATS 3 presenting on weekends or after hours, and those with infectious, gastrointestinal, or neurological conditions warrant careful attention as these factors were associated with higher odds of ICU admission. Ongoing staff education regarding triage and signs of deterioration are important to prevent avoidable outcomes.